FROM PHILANTHROPY TO ECONOMIC TRANSFORMATION: MAUDUI'S TAFSIR APPROACH TO THE CONCEPT OF INFAQ IN THE QUR'AN - Ihrom Jaelani; Moh Najib; Acim (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2026)
This study aims to reconstruct the concept of Infaq from a charitable philanthropy paradigm into a strategic instrument for economic transformation. The phenomenon of persistent structural poverty amid high levels of Islamic philanthropy indicates that Infaq practices have thus far been predominantly consumptive in nature, thereby failing to drive sustainable structural change. Using a qualitative-synthetic approach, this study contextualises the Maudu‘i (Thematic) Interpretation of the verses on Infaq/Nafaqah with the Theory of Economic Transformation and the Maqāṣid Sharīʿah framework. This method finds that Infaq has a dual function: as spiritual purification (Tazkiyah) and as a mechanism for systemic socio-economic intervention (Tanmiyah). The normative synthesis affirms the function of Infaq as mandatory anti-hoarding macroeconomic regulation and a driver of wealth circulation (Multiplier Effect), as well as prioritising family Nafaqah as a basic investment in human capital. These findings are formulated into the Maqāṣid-Based Transformative Infaq Framework. This framework offers four Policy Design Principles, including the Dual-Tier Allocation Principle, which explicitly separates safety net (charitable) funds and Tanmiyah (productive empowerment) funds, as well as Asset Quality Optimisation. Definitively, this study proves that Infaq is a strategic Socio-Economic Financial Intervention Instrument to shift people from consumptive dependence to independence and sustainable economic transformation.